Spirulina platensis and Chlorella vulgaris in practical diets of juvenile African catfish (Clarias gariepinus) / Raji Ameenat Abiodun - Raji Ameenat , Abiodun (2018)
Aquaculture production in natural or controlled marine or freshwater environment is an important industry for food security. Extensive production of African catfish is highly dependent on fishmeal (FM) as the most preferred protein source owing to its well-balanced nutrient properties. However, increasing prices of FM and the need for more secured alternative nutritional sources have aroused significant interest in the use of plants sources, especially the algae. This study evaluated the potential of Spirulina platensis and Chlorella vulgaris in the diets of African catfish (Clarias gariepinus) in relation to nutrient and amino acids digestibility, growth performance, immune-stimulatory and antioxidant properties. Four different feeding trials were conducted with Spirulina (SP) and Chlorella (CL) replacing up to 75% fishmeal (FM) protein contribution in the various feeding trials except for digestibility experiment where the two test diets were formulated using 30% each of the test ingredients (SP and CL) and 70% reference (Ref containing FM and plant feedstuffs) diet on a dry basis. Results obtained from these trials indicated that SP and CL exhibited significantly higher (P<0.05) nutrient and amino acids ADCs than FM experimental group. CL75% best-supported growth and Polynomial curve estimation regression analysis revealed the optimum FM replacement levels by SP and CL to be 68.5% and 69.4% respectively. These levels subsequently served as a guide in feed formulation of immunity and oxidative stress enzymes studies. The effect of SP on flesh fat deposition was found to be dependent on the nutritional composition, the lipid source and quantity (plant/ animal oil) as well as the quantity of SP incorporated into the diets. Comparatively SP75% and CL50% had better haematological and biochemical values pre-and post- Aeromonas hydrophila, than control. Increased supplementation of both algae significantly reduced LDL (58.65- 58.68mg/dl) and enhanced HDL (69.21 – 70.66mg/dl) an indication of their hypocholesterolemic properties. Post-challenge mortalities were significantly decreased in groups treated with both algae (26.67- 53.33%) as compared to control (80%). Significantly highest intestinal (1.29×105 Cfu mlˉ1), and lowest liver (3.72× 102 Cfu mlˉ1) bacteria load was found in the control and CL50% respectively. Also, maximum lysozyme and respiratory burst activity were observed in CL75 (145U mlˉ1) and CL50 (1.55A540) correspondingly. This indicated that the different algae inclusion levels enhanced the immunity and survivability of the African catfish. Replacement of FM by Spirulina and Chlorella in African catfish diet improved CAT and SOD (especially in CL75% and SP75%) activities of the Africa catfish despite the minor effect of GST enzymes. This suggests that substituting FM with 50 – 75 % of SP or CL, in the diets of C. gariepinus, have the potential to improve growth and feed efficiency with no adverse effect on the fish’s well-being. This thesis, therefore, stands to argue that introduction of SP and CL are strongly recommended as a partial replacement for the conventional FM in Africa catfish feed. The introduction of both algae would enhance higher output, improve the revenue base of the entrepreneur in the African catfish industry and increase food animal protein for the consumers.